Cartoon Violence in YouTube Shorts: A Qualitative Content Analysis on Children’s Potential Imitation of Violent Behavior - Melisa Arisanty; Yasir Riady; Selly Anastasia Amelia Kharis; Sri Sukatmi; Majidah Majidah (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2025)
Background: YouTube Shorts has rapidly become one of the most consumed digital formats among children due to its short duration, fast-paced visual stimuli, and algorithm-driven recommendations. While these characteristics make Shorts highly engaging, they also increase the risk of repeated exposure to violent cartoon content, which may influence children’s behavior through imitation and desensitization.Aims: This study aims to identify the forms of violence present in popular YouTube Shorts cartoons and analyze their potential to be imitated by early childhood–aged children, as well as examine the role of YouTube’s algorithm in reinforcing repeated exposure.Method: A qualitative content analysis approach was employed to examine 90 YouTube Shorts videos selected through purposive sampling from three popular categories: Roblox animations, Squid Game parody animations, and Tung-Tung Sahur meme-style animations. Each video was coded based on indicators of physical, symbolic, and verbal violence.Results: All analyzed videos contained recurrent violent cues, with physical chasing sequences accounting for 32%, symbolic harm for 29%, threat-based elimination for 21%, and verbal aggression for 18%. These elements were often presented humorously or as challenges, increasing their likelihood of being imitated by children. Algorithmic reinforcement further intensified exposure by repeatedly recommending similar content, contributing to desensitization and the strengthening of aggressive behavioral scripts.Conclusion: The findings indicate that YouTube Shorts cartoons contribute to the development of aggressive tendencies in young viewers through repeated portrayals of violence. The study underscores the need for stronger parental mediation, improved platform moderation, and digital literacy education. Future research should include larger samples and cross-platform analyses to better understand long-term behavioral impacts.